Residual stress detection of welded parts based on excitation vibration response. (14th February 2020) - Liu, Xiaohan; Shi, Guangfeng
With the rapid development of the equipment industry, people pay more attention to the stress research of materials. However, there is no more suitable and effective method to detect the variation of residual stress. To find an efficient and useful method to analyze the residual stress of the welded parts, this article selects the Q235 component as the research object and produces a detection robot with the core of processing vibration signal and extracting signal data. In combination with the vibration signal extracted by the robot, we study the influence law of the residual stress of the material through numerical simulation and experimental verification. The detection of residual stress is related to the change in the number of taps of the robot and the increase or decrease in the number of taps of the robot. We used the vibration signal extracted by the robot and analyzed the orthogonal parameters of the high-frequency induction welding process parameters to obtain a set of the most unique process parameters: The tapping angle was 7° and the tapping frequency was 300 Hz. We also set up the robot to extract and analyze the vibration signal using four different hammerheads. The results show that the sub-resonance analysis results as the standard, the deviation of the steel head and the aluminum head hammer is about ±10, the result is more accurate, and the frequency of the nylon and plastic hammer is lower, because it is softer. When the hammer is struck, the contact time of the hammerhead with the workpiece is lengthened, so that a lower frequency can be excited.